The Sall2 transcription factor promotes cell migration regulating focal adhesion turnover and integrin β1 expression - Riffo, Elizabeth; Palma, Mario; Hepp, Matías I.; Benítez-Riquelme, Diego; Torres, Vicente A.; Castro, Ariel F.; Pincheira, Roxana (Frontiers in Cell and Developmental Biology, 2022)
SALL2/Sall2 is a transcription factor associated with development, neuronal differentiation, and cancer. Interestingly, SALL2/Sall2 deficiency leads to failure of the optic fissure closure and neurite outgrowth, suggesting a positive role for SALL2/Sall2 in cell migration. However, in some cancer cells, SALL2 deficiency is associated with increased cell migration. To further investigate the role of Sall2 in the cell migration process, we used immortalized Sall2 knockout (Sall2-/-) and Sall2 wild-type (Sall2+/+) mouse embryonic fibroblasts (iMEFs). Our results indicated that Sall2 positively regulates cell migration, promoting cell detachment and focal adhesions turnover. Sall2 deficiency decreased cell motility and altered focal adhesion dynamics. Accordingly, restoring Sall2 expression in the Sall2-/- iMEFs by using a doxycycline-inducible Tet-On system recovered cell migratory capabilities and focal adhesion dynamics. In addition, Sall2 promoted the autophosphorylation of Focal Adhesion Kinase (FAK) at Y397 and increased integrin 1 mRNA and its protein expression at the cell surface. We demonstrated that SALL2 increases ITGB1 promoter activity and binds to conserved SALL2-binding sites at the proximal region of the ITGB1 promoter, validated by ChIP experiments. Furthermore, the overexpression of integrin β1 or its blockade generates a cell migration phenotype similar to that of Sall2+/+ or Sall2-/- cells, respectively. Altogether, our data showed that Sall2 promotes cell migration by modulating focal adhesion dynamics, and this phenotype is associated with SALL2/Sall2-transcriptional regulation of integrin 1 expression and FAK autophosphorylation. Since deregulation of cell migration promotes congenital abnormalities, tumor formation, and spread to other tissues, our findings suggest that the SALL2/Sall2- integrin β1 axis could be relevant for those processes.